Chapter Defining the Hittite "Pantheon", its Hierarchy and Circles: Methodological Perspectives - Warbinek, Livio (Studia Asiana, 2023)
For the Hittite religion of the "Thousand Gods of Hatti" the scholarship has identified different ways of categorization: State pantheon, Local cults, "circle" and numeric group are the most widely used categories based on several criteria, such as linguistics, geography, and cultural milieu. The present paper aims to better define the state of the question about the hierarchy within the Hittite pantheon on the one hand, and to further investigate the notion of "circle" in the Hittite religion on the other, whose analysis has raised some questions and has led to different interpretations.